Rainfastness of Pesticides - Bonnie Wells; Frederick M. Fishel (EDIS, 2011)
Generally, it is best to avoid pesticide application when rainfall is likely; however, weather can be unpredictable, so it is best to choose a product with good rainfast characteristics. Learn more in this 3-page fact sheet written by Bonnie Wells and F.M. Fishel, and published by the UF Department of Agronomy, August 2011.